Exploration of risk factors by applying respectful model among drug addicts of malay ethnic - Merikan Aren; Fatin Farhanah Matjelan (Indonesian Institute for Counseling, Education and Theraphy, 2021)
The purpose of this research is to explore the risk factors by applying respectful Model among drug addicts of Malay ethnic in Sarawak, Malaysia. Data and information were gathered from 3 participants from CCSC, Kuching. Qualitative research methodology is used in this research and the data were collected by using group counselling sessions and audio recorded. The data were analyzed using content analysis from the group counselling sessions and applying respectful Model to achieve final results. The findings have shown that there were risk factors that affect the drug addicts based on domain from respectful Model, Psychological maturity and personal style (P), location of residences (L) and family background (F). Another factor that affects drug addiction is peer pressure. The study contributes to the existing pool of knowledge to the pattern of drug addictions in Malaysia. In addition, it will be useful towards the authorities in identifying the specific factors affecting the drug addicts to reduce the number of relapse and drug addicts. On the other hand, the result of this study could help counsellor to understand the clients that are involved in drug addiction in depth.